Improved Bioavailability of Albendazole Following Oral Administration of Nanosuspension in Rats - Pavan Kumar, Mittapalli; Madhusudan Rao, Yamasani; Apte, Shashank (Current Nanoscience, 2007)
Albendazole, a lipophilic anthelmintic drug, has low solubility and bioavailability. Albendazole nanosuspensions (ABZNS) were developed using different surfactants (Polysorbate 80 & Poloxamer 188) and hydrophilic mucoadhesive polymers (Hydroxypropyl Methylcellulose) by pre-homogenization followed by high pressure homogenization. Particle size and charge measurements were made with a Malvern Zetasizer. Pharmacokinetics of optimized albendazole nanosuspensions after oral administration to conscious Wistar rats was studied. Average size and zeta potential of optimized formulations of albendazole nanosuspensions ranged from 385.7± 4.3 to 576.2 ± 4.8 nm and - 23.5 ± 1.8 to - 40.5 ± 0.8 mV, respectively. Bioavailability of albendazole nanosuspensions was 2.14 to 2.96 fold after oral administration compared with that of control suspension. These results indicate the potential of nanosuspension in improvement of oral bioavailability of lipophilic drugs such as albendazole.
Keywords: Pharmacokinetics